Internal factors of hydrothermal processing grains with using of the principles of MHT-drying - Погожих, Микола Іванович; Пак, Андрій Олегович; Міщенко, Тетяна Володимирівна; Жеребкін, Максим Васильович (Eastern-European Journal of Enterprise Technologies, 2011)
The intrinsic factors (primary commodities, duration of steep and cooking, temperature of cooking) of hydrothermal processing of grain with application of principles of mixed heat transfer drying were researched